‘Alī bin al-Ḥusayn’s View on Asceticism: Analysis and Review with a Mystical Approach - Vahid Mahmoudi; Maryam Cheraghi (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2022)
Asceticism as a lifestyle is highly esteemed by leaders, scholars, and mystics due to its prominent position in Islam. A survey into the lifestyle of the most significant historical religious figures of the Islamic world shows their detachment from the world and luxurious living. The main question of the research is around this issue in the thought of one of the descendant of Prophet Muhammad whether his noble behavior is the same as asceticism in mystical texts and to know whether asceticism is wearing old clothes, poverty, and abstaining from the lawful blessings. This article intends to explore the concept of asceticism based on content analysis and by referring to main Islamic mysticism texts as well as ‘Alī bin al-Ḥusayn. Asceticism has effects and signs that are mentioned in some words of ‘Alī bin al-Ḥusayn, such as avoiding the apparent, yearning for death and eternal reward of the Hereafter, and striving to obey God. We have discovered and analyzed these words and compared them with its mystical concept. The result of the study indicates the main approach of ‘Alī bin al-Ḥusayn towards the world and emphasizes that Muslim mystics follow the Prophet and his lineage in their ascetic method.